Perbedaan Ankle Brachial Index (ABI) pada Pasien Diabetes Melitus Tipe 2 Obese dan Normal Weight di RSUD Dr. Moewardi - Miranti, Biltinova Arum; Sugiarto, .; Widardo, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Peripheral Arterial Disease (PAD) is one of the complications of type 2 diabetes mellitus. Obesity is a risk factor of PAD and it is estimated 80 - 90% of patients with type 2 diabetes mellitus are overweight or obese. ABI is a simple method for diagnosing PAD and the ABI value of < 0.9 means that the patient suffers PAD. The aims of this study are to know the difference of ABI between obese and normal weight patients with type 2 diabetes mellitus in Dr. Moewardi Hospital and the correlation between ABI and the Body Mass Index (BMI). Methods: This study is an analytical observation by means of cross sectional approach. The subjects were patients of Dr. Moewardi Hospital registered from April to July 2013, suffering type 2 diabetes mellitus. Subjects were selected through purposive sampling. The data were obtained by measuring the patientsâ BMI, examining the patientsâ ABI and checking the patientsâ medical record. The data were analyzed by the unpaired t test, significant if p value < 0.05, and by Spearman correlation test through SPSS 20.0 Statistic program for Windows. Results: Data were taken from 33 subjects consisting of 11 obese patients and 22 normal weight patients suffering type 2 diabetes mellitus. The result obtained shows that 9 patients were included in the borderline category of ABI values, 6 (66.7%) patients were obese and 3 (33.3%) patients had normal weight. The unpaired t test shows that the mean of ABI of obese vs normal weight patients with type 2 diabetes mellitus is 0.98 Â± 0.06 vs 1.01 Â± 0.06, p = 0.221. The Spearman correlation test between ABI and BMI shows p = 0.028 and r = -0.384. Conclusions: The study suggested that there is no significant difference mean of ABI between obese and normal weight patients with type 2 diabetes mellitus in Dr. Moewardi Hospital. However, based on the interpretation of ABI values ââobtained, the percentage of subjects with lower ABI values ââwas found greater in obese patients with type 2 diabetes mellitus (66.7%). There is correlation between ABI and BMI. Keywords: ABI, obese type 2 diabetes mellitus, normal weight type 2 diabetes mellitus Â